2020
DOI: 10.1016/j.bjorl.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation of the Amsterdam inventory for auditory disability and handicap to Brazilian Portuguese

Abstract: The English version of the Amsterdam inventory for auditory disability and handicap could be translated and adapted to Brazilian Portuguese. An analyses of the validation process yielded reliable, consistent, and stable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
3
0
4
Order By: Relevance
“…Fuente et al 29 suggested that the AIADH should be used in hearing conservation programs to screen for possible negative auditory outcomes due to solvent exposure that are not detected by pure-tone audiometry. The AIADH was initially developed in Dutch and English 48 and later adapted into Spanish, 50 Cantonese, 51 Portuguese, 52 and Turkish. 53 …”
Section: Discussionmentioning
confidence: 99%
“…Fuente et al 29 suggested that the AIADH should be used in hearing conservation programs to screen for possible negative auditory outcomes due to solvent exposure that are not detected by pure-tone audiometry. The AIADH was initially developed in Dutch and English 48 and later adapted into Spanish, 50 Cantonese, 51 Portuguese, 52 and Turkish. 53 …”
Section: Discussionmentioning
confidence: 99%
“…10 After psychometric testing, Kramer et al 11 modified the AIADH (denoted as (m)AIADH) and excluded two items to enhance reliability and validity. The (m)AIADH has been tested in many research studies and validated in various languages, including Swedish, Spanish, Turkish, Portuguese, and Cantonese, [12][13][14][15][16] but not in English. It has also not been applied and tested for the firefighter population in any earlier studies.…”
Section: Introductionmentioning
confidence: 99%
“…Esses processos devem ser conduzidos para que seja atingido um resultado confiável, preciso, compreensível e dentro dos aspectos culturais da população-alvo (15) . Acrescido a isso, acarretam maior acurácia na mensuração de aspectos inerentes à população em questão, menores esforços, tempo e recursos financeiros, quando comparados à criação de um novo instrumento, bem como proporcionam a comparação de resultados entre diferentes amostras, permitindo a realização de estudos transculturais utilizando o mesmo instrumento (16) . Nesse contexto, o presente estudo teve como objetivo a tradução e adaptação cultural do Hearing Aid Skills and Knowledge Test (HASK) para o português do Brasil.…”
Section: Introductionunclassified